Secondary Glioblastoma Multiforme in a Child with Disseminated Juvenile Pilocytic Astrocytoma. (19th November 2012) - Amene, C. S.; Yeh-Nayre, L. A.; Crawford, J. R.
Abstract : Secondary glioblastoma multiforme (sGBM) can occur after a long latency period following radiation treatment of various diseases including brain tumors, leukemia, and more benign disorders like tinea capitis. Outcomes of radiation-induced sGBM remain poor in both children and adults. We report a case of a 16-year-old girl with a history of disseminated juvenile pilocytic astrocytoma treated with chemotherapy and craniospinal radiation 9 years prior who developed sGBM in the absence of a tumor predisposition syndrome. She presented with a several-week history of headaches and no acute findings on computed tomography compared to baseline neuroimaging 3 months prior. Repeat computed tomography performed just 3 weeks later for worsening headaches revealed a new large posterior fossa tumor where pathology confirmed the diagnosis of sGBM. In spite of maximal surgical resection, reirradiation, and adjuvant chemotherapy, she died 1 year postdiagnosis. Our case highlights the potential late effects of high-dose cranial radiation, how symptomatology may precede neuroimaging findings, and the rapid formation of sGBM that mirrors that of de novo Glioblastoma Multiforme.